2-й Международный семинар по физике низких температур в условиях микрогравитации (CWS-99) - Межов-Деглин, Л.П. (Физика низких температур, 2000)
The International Seminar CWS-99, devoted to a discussion of the current status and prospects for development of fundamental research in the field of low-temperature physics in a microgravity environment, was held in at the Research Center of the Russian Academy of Sciences (RCC RAN) in Chernogolovka, Moscow District on July 28–August 2, 1999. This seminar was organized by the Institute of Solid State Physics and the Space Materials Science section of the Space Council of the Russian Academy of Sciences with the financial support of the Russian Fund for Fundamental Research, the Ministry of Science and Technology of the Russian Federation, The Russian Aviation & Space Agency, and the Council on Low Temperature Physics of the Russian Academy of Sciences. The CWS-99 Seminar preceded the International Conference on Low Temperature Physics LT-22, and, as one of the satellite activities of LT-22 conducted in the framework of international scientific cooperation, it received substantial support from the Organizing Committee of LT-22 and from the OLMSA Division of the National Aeronoutics and Space Administration (NASA), USA.